Advances in ergonomics in manufacturing - Karwowski, Waldemar , 1953-; Trzcielinski, Stefan (Advances in human factors and ergonomics series, 2013)
"Meeting the needs of the manufacturing and service sectors of contemporary industry, this volume is concerned with the human factors, ergonomics, and safety issues related to the design of products, processes, and systems, as well as the operation and management of business enterprises. This book will be of special value to researchers and practitioners involved in the design of products, processes, systems, and services, which are marketed and utilized by a variety of organizations around the world" -- Provided by publisher